LAJU PENGERINGAN GABAH MENGGUNAKAN PENGERING TIPE EFEK RUMAH KACA (ERK) - Ramli, Ida Amalia; Jamaluddin P, Jamaluddin P; Yanto, Subari (Universitas Negeri Makassar, 2017)
The purpose of this research is to know the rate of drying of grain using dryers of Greenhouse effect type. This research is a type of experimen research by drying of grain for 7 hours. During the drying process, conducted temperature measurement of on the dryer room is using a thermometer. In addition, to determine changes water content conducted water content test before and after drying use oven method. The results showed that the initial water content of the in grain that is 24.21% (bb). The of in grain highest drying rate occurs at the beginning of drying is in the 30th minute water evaporate at 0.17% (bb/mt). Drying rate continues to occur, but along with the increase drying time and increasingly dryness of the ingredients so that in the final stages the water evaporates approach 0 with the final water content obtained that is 7.24% (bb)